2021
DOI: 10.1186/s40168-021-01091-0
|View full text |Cite
|
Sign up to set email alerts
|

Indoor bacterial, fungal and viral species and functional genes in urban and rural schools in Shanxi Province, China–association with asthma, rhinitis and rhinoconjunctivitis in high school students

Abstract: Background Studies in developed countries have reported that the prevalence of asthma and rhinitis is higher in urban areas than in rural areas, and this phenomenon is associated with urbanization and changing indoor microbiome exposure. Developing countries such as China have experienced rapid urbanization in past years, but no study has investigated microbiome exposure and urban-rural health effects in these countries. Methods Nine high schools f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 67 publications
6
28
1
Order By: Relevance
“…According to the PCoA analysis, suburban homes had a distinct bacterial community, while the pig and cow farmers’ homes showed a minor overlap ( Figure 3 ). Different indoor bacterial community composition between suburban and farmers’ homes is in line with previous studies, which showed a difference in microbiota between farm and non-farm homes ( Kirjavainen et al, 2019 ; Fu et al, 2021 ). Even though there is an overlap in the community composition of cow and pig farmers’ homes, there was a significant difference in the community composition between cow and pig farmers’ homes.…”
Section: Discussionsupporting
confidence: 91%
“…According to the PCoA analysis, suburban homes had a distinct bacterial community, while the pig and cow farmers’ homes showed a minor overlap ( Figure 3 ). Different indoor bacterial community composition between suburban and farmers’ homes is in line with previous studies, which showed a difference in microbiota between farm and non-farm homes ( Kirjavainen et al, 2019 ; Fu et al, 2021 ). Even though there is an overlap in the community composition of cow and pig farmers’ homes, there was a significant difference in the community composition between cow and pig farmers’ homes.…”
Section: Discussionsupporting
confidence: 91%
“…The libraries were sequenced on the Illumina HiSeq X-ten platform. The raw sequencing reads were processed to obtain quality-filtered reads for further analyses followed by co-occurrence network analyses as reported previously (Zhang et al, 2018;Fu et al, 2021).…”
Section: Analyses Of Effects Of Talaromyces Purpurogenus Q2 On Soil Microecology and Abundance Of F Oxysporummentioning
confidence: 99%
“…In the period between 2019 and 2022, only one relevant article was found related to the safety of M. foliorum. Fu et al (2021) studied the microbiological load of urban air dust by a metagenomic approach and found an association of M. foliorum with the occurrence of wheeze, rhinitis and rhinoconjunctivitis; a causal relationship was not investigated.…”
Section: Microbacterium Foliorummentioning
confidence: 99%